Does craniofacial morphology relate to sleep apnea severity reduction following weight loss intervention? A patient-level meta-analysis. Issue 3 (12th October 2020) - Sutherland, Kate; Chapman, Julia L; Cayanan, Elizabeth A; Lowth, Aimee B; Hoyos, Camilla M; Wong, Keith K H; Yee, Brendon J; Grunstein, Ronald R; Cistulli, Peter A; Marshall, Nathaniel S
Abstract: Study Objectives: Obesity is a common and reversible risk factor for obstructive sleep apnea (OSA). However, there is substantial unexplained variability in the amount of OSA improvement for any given amount of weight loss. Facial photography is a simple, inexpensive, and radiation-free method for craniofacial assessment. Our aims were (1) to determine whether facial measurements can explain OSA changes, beyond weight loss magnitude and (2) whether facial morphology relates to how effective weight loss will be for OSA improvement. Methods: We combined data from three weight loss intervention trials in which participants had standardized pre-intervention facial photography ( N = 91; 70.3% male, mean ± SD weight loss 10.4 ± 9.6% with 20.5 ± 51.2% apnea–hypopnea index [AHI] reduction). Three skeletal-type craniofacial measurements (mandibular length, lower face height, and maxilla-mandible relationship angle) were assessed for relationship to AHI change following weight loss intervention. Results: Weight and AHI changes were moderately correlated (rho = 0.3, p = 0.002). In linear regression, an increased maxilla-mandible relationship angle related to AHI improvement ( β [95% CI] −1.7 [−2.9, −0.5], p = 0.004). Maxilla-mandible relationship angle explained 10% in the variance in AHI over the amount predicted by weight loss amount (20%). The relationship between weight change and AHI was unaffected by the maxilla–mandible relationship angle (interaction term p > 0.05). Conclusions: Regardless of facial morphology, weight loss is similarly moderately predictive of OSA improvement. Increased maxilla-mandible relationship angle, suggestive of retrognathia, was weakly predictive of OSA response to weight loss. Although this is unlikely to be clinically useful, exploration in other ethnic groups may be warranted.